Menstrual Hygiene Management Practices & Challenges Among Women in Wetland Areas of Riau: a Qualitative Study - Masrina Munawarah Tampubolon; Yulia Irvani Dewi; Misrawati Misrawati; Sri Utami (Jurnal Ners, 2025)
Menstrual Hygiene Management (MHM) remains understudied among women living in wetland environments, despite their vulnerability to limited access to clean water and sanitation. This study aimed to explore the practices, needs, and challenges in menstrual hygiene management among reproductive-age women residing in the wetland areas of Riau, Indonesia. A qualitative phenomenological design was employed. Data were collected through semi-structured interviews with six women aged 19–42 years, and triangulated with two additional informants (a community health nurse and a participant’s mother). Colaizzi’s method was used for data analysis.Two major themes emerged: (1) Adaptation to environmental constraints—women utilized existing water sources (rivers, boreholes) and followed inherited traditions for menstrual hygiene, including unsafe disposal of sanitary pads; (2) Strategies to maintain reproductive health—women managed discomfort through herbal remedies, self-treatment, and informal social support. However, myths and lack of accurate knowledge persisted. Women in wetland areas manage menstruation through improvised practices shaped by environmental and socio-cultural factors. There is a pressing need for culturally sensitive reproductive health education, improved access to WASH facilities, and sustainable sanitary waste disposal systems